Does Watching an English Movie Enable the Students to Write Essays? (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Watching movies has been regarded as an effective activity to help students improve their writing skills, especially in essay writing. The purpose of this study was to examine the effect of watching an English movie on students’ essay writing skills, as well as to investigate students' perceptions of this activity. The study involved thirty-nine students from STMIK Jayanusa. This research employed a mixed-methods design, incorporating both quantitative and qualitative data. Essay writing tests were conducted in the form of a pretest and a posttest. The test results were analyzed and compared using SPSS, with a t-test applied to measure the effect of watching an English movie on students’ writing skills. Additionally, students' perceptions of watching English movies were gathered through interviews, which were then analyzed using Nvivo software. The results revealed that the students' posttest mean scores were significantly higher than their pretest scores, indicating an improvement in their essay writing skills. The t-test results confirmed that watching an English movie had a positive effect on students’ essay writing skills. In terms of perceptions, the students expressed positive views on the activity, with many agreeing that watching English movies helped them write more structured essays. The social issues presented in the movies provided context for their writing, while the exposure to new vocabulary and grammar structures enhanced their language proficiency. Overall, the study suggests that watching English movies is an effective tool for improving essay writing skills, as it not only enhances students’ understanding of language structure but also engages them in meaningful content that can be applied to their writing tasks. The research underscores the importance of integrating multimedia resources into language learning, particularly in writing instruction.